TES BAKAT NUMERIKAL UNTUK MEMPREDIKSI PRESTASI BELAJAR MATEMATIKA SISWA SMA - Arjanto, Paul (JURNAL KONSELING GUSJIGANG, 2017)
A numerical aptitude test is a test designed to identify how well a person can understand ideas and concepts expressed in the form of numbers and how easily one can think and solve the problems stated in the form of numbers. Mathematics learning achievement is the mastery of knowledge or numeracy skills that appear from the results / achievements learned by high school students. The study used quantitative design with the number of subjects 154 high school students. The instrument used is Differential Apptitude Test (DAT). The result of statistical test by using linear regression analysis shows that the achievement of learning mathematics of high school students is significantly influenced by numerical talent ability with regression equation as follows: mathematics learning achievement = 8,084 + (2,549 x numerical talent).